FEEDING BEHAVIOUR OF DIFFERENT INDIAN BROWN PLANT HOPPER, Nilaparvata lugens (Stal) (Hemiptera: Delphacidae) POPULATIONS ON RESISTANT VARIETIES OF RICE - M. SAMPATH KUMAR; G.R. KATTI, V. SUNIL, V. JHANSI LAKSHMI*, K. CHIRANJEEVI, J.S. BENTUR (The Journal of Research, PJTSAU, 2019)
The virulence levels of different Brown planthopper (BPH) Nilaparvata lugens (Stål) populations collected from Ludhiana (Punjab), West Godavari (Andhra Pradesh) and Nalgonda (Telangana) regions of India against popular resistant rice cultivars in terms of honeydew excretion by BPH females were assessed. Populations and varieties have shown significant difference in honeydew excretion where Ludhiana population showed highest honeydew excretion followed by Nalgonda and West Godavari. In the varieties, highest honeydew excretion was noticed on TN1 and lowest on PTB-33.